2012
DOI: 10.1590/s1519-99402012000100021
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho ponderal de cordeiros Santa Inês e F1 Dorper x Santa Inês em pastagens naturais

Abstract: Objetivou-se com o trabalho avaliar o desempenho ponderal de dois genótipos de ovinos, Santa Inês e F1 Dorper x Santa Inês em pastagem de Panicum maximum cv. Massai. Foram utilizados oito fêmeas e oito machos, de cada genótipo, em delineamento inteiramente casualizado, em esquema fatorial 2x2x2 (dois genótipos, dois sexos e duas idades de abate). Os dados foram submetidos à análise de variância com aplicação do teste de Scot-Knott com probabilidade de 5%. Avaliaram-se peso ao nascimento, peso a desmama, peso f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
1
1
4
Order By: Relevance
“…For instance, the average value of BW in the present study is within the range of 3 to 4 kg found by COSTA et al ( 2012), KORITIAKI et al (2013), SUPAKORN et al (2013), andPERUZZI et al (2015). On the other hand, the mean of WW was lower than the values reported in Santa Inês sheep by COSTA et al (2012) andPERUZZI et al (2015), which were 17.09 (weaning at 90 days of age) and 11.9 kg (mean weight of males weaned at 45 or 60 days of age), respectively. Considering the WW for females, our values were higher than those reported by PERUZZI et al (2015), for lambs weaned at 45 (8.9 kg) or 60 days of age (10.1 kg).…”
Section: Resultscontrasting
confidence: 64%
“…For instance, the average value of BW in the present study is within the range of 3 to 4 kg found by COSTA et al ( 2012), KORITIAKI et al (2013), SUPAKORN et al (2013), andPERUZZI et al (2015). On the other hand, the mean of WW was lower than the values reported in Santa Inês sheep by COSTA et al (2012) andPERUZZI et al (2015), which were 17.09 (weaning at 90 days of age) and 11.9 kg (mean weight of males weaned at 45 or 60 days of age), respectively. Considering the WW for females, our values were higher than those reported by PERUZZI et al (2015), for lambs weaned at 45 (8.9 kg) or 60 days of age (10.1 kg).…”
Section: Resultscontrasting
confidence: 64%
“…Silva et al (2006) evaluated fodder salts of the same dicot species and also reported lower ADG values (109.52 and 85.19 g day -1 ) than the ones found in this study. Similarly, Sousa (2014), Costa et al (2012), and Manera et al (2014) also reported lower ADG values than the value reported in the current study.…”
Section: Parametersupporting
confidence: 50%
“…Os estudos realizados com os cordeiros da raça Dorper estão relacionados a aspectos zootécnicos, bem como, de produção do animal, sendo analisados o desempenho (ARAÚJO FILHO et al, 2010;AMARAL et al, 2011;COSTA et al, 2012), as características de carcaça (CARTAXO et al, 2011a;CARTAXO et al, 2011b;SANTANA et al, 2013), a qualidade da carne (FREIRE et al, 2010;PEIXOTO et al, 2011), o comportamento ingestivo (SCHWARZ et al, 2012;LIMA et al, 2014a), dentre outros, não havendo pesquisas que descrevam as características fenotípicas relatadas neste estudo.…”
Section: Resultsunclassified